Investigation of joint angle specificity in low-load hip abductor isometric training: a randomized controlled trial - Hiroki Tanaka; Tome Ikezoe; Hiroshige Tateuchi; Masatoshi Nakamura; Jun Umehara; Kosuke Fujita; Kojiro Araki; Ko Yanase; Noriaki Ichihashi (Japanese Society of Physical Fitness and Sports Medicine, 2019)
Recently, it was suggested that the angle at which the maximum muscle strength improves depends on the load of training. This is inconsistent with the principle of specificity of joint angle, which indicates that the improvement of muscle strength is obtained when a similar joint angle as the trained angle is used. The present study investigated the angle at which maximum muscle strength increases with low-load hip abductor isometric training. Sixteen healthy men (24.8 ± 3.2 years of age) were randomly divided into an intervention group or a control group. The intervention group performed isometric resistance training for hip abductor muscle at a low intensity of 30% of the maximum voluntary contraction (MVC) at 25° hip abduction three days a week for four weeks. In pre- and post-training, isometric hip abduction MVCs were measured every 10° through the range of hip joint positions from 15° adduction to 35° abduction (i.e. 6 hip angles). A significant interaction was shown only at the hip position of 15° abduction (F = 4.84). At 15° abduction, there was a significant increase in MVC between pre- and post-training for the intervention group (p = .03, d = .53), but not for the control group. Our results indicate that, in low-load hip abductor isometric training, the improvement of the MVC did not follow the specificity of the joint angle. Instead, the low-load training improved the MVC at a joint angle where the muscle is extended further than that during training.